2006
DOI: 10.1007/s10858-006-9077-y
|View full text |Cite
|
Sign up to set email alerts
|

Random sampling of evolution time space and Fourier transform processing

Abstract: Application of Fourier Transform for processing 3D NMR spectra with random sampling of evolution time space is presented. The 2D FT is calculated for pairs of frequencies, instead of conventional sequence of one-dimensional transforms. Signal to noise ratios and linewidths for different random distributions were investigated by simulations and experiments. The experimental examples include 3D HNCA, HNCACB and (15)N-edited NOESY-HSQC spectra of (13)C (15)N labeled ubiquitin sample. Obtained results revealed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 37 publications
3
90
0
Order By: Relevance
“…While this paper was in review, a study by Kazimierczuk et al presenting results for FT processing of randomly distributed sampling points was published [46]. It would be interesting to compare all of these methods in the future.…”
Section: Comparison To Other Sparse Sampling Methodsmentioning
confidence: 98%
“…While this paper was in review, a study by Kazimierczuk et al presenting results for FT processing of randomly distributed sampling points was published [46]. It would be interesting to compare all of these methods in the future.…”
Section: Comparison To Other Sparse Sampling Methodsmentioning
confidence: 98%
“…It has been shown that the FT of randomly sampled twodimensional time domain signals produces some noise, which is reduced proportionally to the square root of the number of data points. 28 In the conventional and randomly sampled examples shown here the same number of correlation signals was observed. The 'sampling noise' is shown on the traces plotted in Figs 3 and 4.…”
Section: Resultsmentioning
confidence: 73%
“…27 This method was initially applied to radial and spiral sampling, and was later extended to random sampling of the evolution time space. 28 In the case of 3D acquisition, a one-dimensional FID is recorded for each point in the two-dimensional time space with four different modulations in order to fulfill the quadrature requirements. The most important features of the new method are calculation of FT for each pair of frequencies simultaneously and the use of Quaternion notation to describe double quadrature detection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the two dimensional Fourier transformation (2D-FT) has been re-introduced to transform arbitrarily sampled time domain signals [3][4][5]. In principle the 2D-FT allows the use of non-linear time domain sampling.…”
Section: Introductionmentioning
confidence: 99%